Tejiendo la red inquisitorial. Las confesiones del converso Francesc Joan como instrumento para la incoación procesal de un amplio grupo de conversos valencianos - Jacob Mompó Navarro (Mélanges de la Casa de Velázquez, 2024)
In 1520, the convert Francesc Joan faced an inquisitorial process, accused of Judaizing. The actions of which he was accused dated back almost twenty years, during the Fast of Forgiveness. Judging by his confessions, that Yom Kippur celebration in Valencia must have been multitudinous, since, appealing to his portentous memory, the defendant metionned around 350 people in his statements. True or not, his confessions were used to open numerous inquisitorial processes against many of the people he denounced. In our work we analyse the process against Francesc Joan, as well as some interconnections existing in other processes against converts.